Crisis averted: a world united against the menace of multiple drug-resistant superbugs -pioneering anti-AMR vaccines, RNA interference, nanomedicine, CRISPR-based antimicrobials, bacteriophage therapies, and clinical artificial intelligence strategies to safeguard global antimicrobial arsenal - Saeed, Umar; Insaf, Rawal Alies; Piracha, Zahra Zahid; Tariq, Muhammad Nouman; Sohail, Azka; Abbasi, Umer Ali; Fida Rana, Muhammad Shahmeer; Gilani, Syed Shayan; Noor, Seneen; Noor, Elyeen; Waheed, Yasir; Wahid, Maryam; et al. (Frontiers in Microbiology, 2023)
The efficacy of antibiotics and other antimicrobial agents in combating bacterial infections faces a grave peril in the form of antimicrobial resistance (AMR), an exceedingly pressing global health issue. The emergence and dissemination of drug-resistant bacteria can be attributed to the rampant overuse and misuse of antibiotics, leading to dire consequences such as organ failure and sepsis.Beyond the realm of individual health, the pervasive specter of AMR casts its ominous shadow upon the economy and society at large, resulting in protracted hospital stays, elevated medical expenditures, and diminished productivity, with particularly dire consequences for vulnerable populations. It is abundantly clear that addressing this ominous threat necessitates a concerted international endeavor encompassing the optimization of antibiotic deployment, the pursuit of novel antimicrobial compounds and therapeutic strategies, the enhancement of surveillance and monitoring of resistant bacterial strains, and the assurance of universal access to efficacious treatments. In the ongoing struggle against this encroaching menace, phage-based therapies, strategically tailored to combat AMR, offer a formidable line of defense. Furthermore, an alluring pathway forward for the development of vaccines lies in the utilization of virus-like particles (VLPs), which have demonstrated their remarkable capacity to elicit a robust immune response against bacterial infections. VLP-based vaccinations, characterized by their absence of genetic material and non-infectious nature, present a markedly safer and more stable alternative to conventional immunization protocols. Encouragingly, preclinical investigations have yielded promising results in the development of VLP vaccines targeting pivotal bacteria implicated in the AMR crisis, including Salmonella, Escherichia coli, and Clostridium difficile. Notwithstanding the undeniable potential of VLP vaccines, formidable challenges persist, including the identification of suitable bacterial markers for vaccination and the formidable prospect of bacterial pathogens evolving mechanisms to thwart the immune response. Nonetheless, the prospect of VLP-based vaccines holds great promise in the relentless fight against AMR, underscoring the need for sustained research and development endeavors. In the quest to marshal more potent defenses against AMR and to pave the way for visionary innovations, cutting-edge techniques that incorporate RNA interference, nanomedicine, and the integration of artificial intelligence are currently under rigorous scrutiny.